Influence of Influencer Credibility and Visual Content on Gen Z's TikTok Purchase Intention - Nadya Aurelle Dwisyah; Defa Enggrina; Delta Pelangi; Asmita Wulansari Dg. Liwang (IECON: International Economics and Business Conference, 2025)
This study investigates the impact of influencer credibility and visual content on the purchase intention of Generation Z users on TikTok. Given the rising influence of social media marketing and the unique behaviors of Gen Z, understanding these factors is critical for effective digital marketing strategies. The research aims to examine how perceived trustworthiness, expertise, and attractiveness of influencers, alongside the quality and appeal of visual content, affect purchase intentions. A quantitative approach was employed, utilizing a structured questionnaire distributed to 350 Gen Z TikTok users selected through purposive sampling. Data were analyzed using structural equation modeling (SEM) to assess the relationships between variables. The results reveal that both influencer credibility and visual content significantly influence purchase intention, with influencer credibility showing a stronger effect. The findings suggest that marketers should prioritize building authentic and trustworthy influencer partnerships, as well as optimizing visual content to engage Gen Z audiences effectively. This study contributes to the growing body of knowledge on social media marketing by highlighting the specific drivers of purchase behavior on emerging platforms like TikTok. The implications offer valuable insights for marketers seeking to enhance consumer engagement and drive sales through influencer collaborations and compelling visual storytelling. The study recommends further research on other social media platforms and additional factors affecting Gen Z’s consumer behavior.